Land management through conservation agriculture and associated practices - Thierfelder, Christian L. (CAB International, 2022)
This chapter presents conservation agriculture, which can help smallholder farmers build better resilience to the consequences of climate change and variable weather (including persistent droughts and unseasonal dry spells). It addresses challenges to crop productivity and profitability while promoting sustainable land use and supporting ecosystem services. Conservation agriculture is based on the principles of minimum soil disturbance, crop residue retention, and crop rotation.